PUSAT SENI BELADIRI KUNTAU DI DESA BARIKIN - Azmi, Muhammad Mustaqim; Muchamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
The Kuntau Martial Arts Center in Barikin Village is a facility that accommodates the local community in learning, developing and preserving the local Banjar martial arts. The architectural problem raised in this report is how the design of the banjar’s typical kuntau martial arts center can accommodate training activities and kuntau performances. The concept proposed for the design is the concept of a Cultural Education Recreation with a Vernakular-based Regional Architecture approach. This Concept raises the character of kuntau culture and banjar culture into the form of kuntau martial arts center building